2023
DOI: 10.1126/sciadv.add5668
|View full text |Cite
|
Sign up to set email alerts
|

In situ modulation of intestinal organoid epithelial curvature through photoinduced viscoelasticity directs crypt morphogenesis

Abstract: Spatiotemporally coordinated transformations in epithelial curvature are necessary to generate crypt-villus structures during intestinal development. However, the temporal regulation of mechanotransduction pathways that drive crypt morphogenesis remains understudied. Intestinal organoids have proven useful to study crypt morphogenesis in vitro, yet the reliance on static culture scaffolds limits the ability to assess the temporal effects of changing curvature. Here, a photoinduced hydrogel cross-link exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The intestinal epithelium consists of a singular layer of columnar epithelial cells that are arranged in a specific order, with several specialized cells possessing unique properties and functions such as intestinal epithelial cells (IECs), goblet cells, intestinal microfold (M) cells, and Paneth cells. [53][54][55][56] IECs play a critical role in absorbing various small molecules and have the capability of transporting immunoglobulin A produced by plasma B cells in the lamina propria to the intestinal lumen, which helps to maintain the overall stability of the intestinal epithelium. 48,57 Furthermore, IECs play an active role in local immune responses.…”
Section: Epithelium Barriers and Tight Junctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal epithelium consists of a singular layer of columnar epithelial cells that are arranged in a specific order, with several specialized cells possessing unique properties and functions such as intestinal epithelial cells (IECs), goblet cells, intestinal microfold (M) cells, and Paneth cells. [53][54][55][56] IECs play a critical role in absorbing various small molecules and have the capability of transporting immunoglobulin A produced by plasma B cells in the lamina propria to the intestinal lumen, which helps to maintain the overall stability of the intestinal epithelium. 48,57 Furthermore, IECs play an active role in local immune responses.…”
Section: Epithelium Barriers and Tight Junctionsmentioning
confidence: 99%
“…The secretions of Paneth cells contain lysozyme, phospholipase A2, and a-defensins, all of which have antibacterial functions. 55 Impairment in the function of the intestinal mucosal barrier, particularly the dysfunction of Paneth cells, plays a significant role in initiating and advancing IBD. Recent research proposes that Paneth cells act as the primary site for the onset of IBD, influencing intestinal inflammatory responses through the release of antimicrobial peptides (AMPs).…”
Section: Epithelium Barriers and Tight Junctionsmentioning
confidence: 99%
“…Dynamic covalent chemistries have been employed for the cross-linking of hydrogels, resulting in a reversible gelation process. 106,129,130 Beside thiol exchange chemistry, a variety of other chemistries have been explored for the purpose of 3D cell culture applications, including the utilization of boronate ester, hydrazone, Diel-Alder, Oxime, and imine. 106 There is an increasing interest in the utilization of dynamic covalent cross-linking techniques for the creation of hydrogels with a dynamic polymeric network that exhibits plastic deformation in response to forces applied by cells.…”
Section: Dynamic Covalent Cross-linkingmentioning
confidence: 99%
“…The key advantage of photo-induced hydrogel modulation is the precise spatiotemporal regulation of chemical reactions within the hydrogel. Utilizing photo-induced allyl sulfide exchange reactions, Yavitt et al 130 demonstrated the capability to spatiotemporally control the cross-linking of PEG-based hydrogels and modulate the shape of intestinal organoids to direct crypt morphogenesis. As this chemistry is far from the topic of this thesis, the reader is encouraged to study some of the recent review articles covered this topic.…”
Section: Photoinduced Hydrogel Modulaitonmentioning
confidence: 99%
“…However, altering the viscoelasticity of a hydrogel in time or space, for example, the rate at which stress relaxes under constant strain without simultaneously altering the stiffness, remains a challenge. Very recently, this challenge was overcome using PEG gels and a method that enables light-triggered exchange of cross-link bonds to permit stress relaxation, enabling control of viscoelasticity. , Here, we demonstrate a strategy to spatiotemporally modulate 3D alginate hydrogel stress relaxation without altering stiffness and in the presence of cells. Our platform utilizes alginate gels cross-linked with calcium, which are inherently viscoelastic due to the nature of the ionic bonds.…”
Section: Introductionmentioning
confidence: 99%